Implementasi Program Pos Upaya Kesehatan Kerja (UKK) di Wilayah Kerja Puskesmas Tahtul Yaman Kota Jambi - Faridah, Faridah; Hasmar, Wanti (Jurnal Akademika Baiturrahim Jambi, 2025)
According to information from the program holder, the Occupational Safety Post at the Tahtul Yaman Community Health Center in Jambi was established in 2021 under the name Kapal Sanggat UKK Post. In 2023, the "Kapal Sanggat" UKK Post Program implemented innovative services focused on batik artisans experiencing musculoskeletal disorders. The purpose of this study was to analyze the implementation of the UKK Post for musculoskeletal disorders in batik workers in the Tahtul Yaman Community Health Center (Puskesmas) in Jambi City in 2024. This research method was a qualitative descriptive study using in-depth interviews, observation, and document review techniques. The results showed that the Tahtul Yaman Community Health Center had implemented an innovative UKK Post program in its work area, focusing on batik workers experiencing musculoskeletal disorders. Activities that had been carried out included counseling about the UKK Post and health checks, but these were not yet routinely conducted. Curative and rehabilitative activities only included elderly gymnastics and stretching exercises. It is recommended that the Community Health Center provide regular guidance, monitoring, and evaluation of the implementation of activities at the Kapal Sanggat UKK Post, conduct training for health workers and cadres, and provide supporting facilities and infrastructure